An analysis of slang word in song lyrics by travis scott on astroworld album - Tanamal, Gabrielle Sarah Maria; Juniartha , I Wayan; Ariyaningsih, Ni Nyoman Deni (Journal of Language and Applied Linguistics, 2020)
This study entitled An Analysis of Slang Word in Song Lyrics by Travis Scott on Astroworld Album is intended to find out the types of slang word that used in Song Lyrics by Travis Scott. The analysis concerns with the Slang words that occur in Song Lyrics on Astroworld Album. This study used qualitative technique and Descriptive study in textual analysis to elaborate the various types that occur in song lyrics on Astroworld Album. Theory used in this analysis is Theory by Yule (1986) which to find out the kinds or type of slang word that occurs in the song lyric by Travis Scott on Astroworld album. The study concludes that the clipping slang words are mostly used and the least type of slang word used in the Astroworld album is derivation, borrowing and back formation in the song lyrics on Astroworld Album.